Transfer Pricing Aggressiveness in Indonesia: Multinationality, Tax Haven, and Intangible Assets - Irawan, Ferry; Ulinnuha, Imla Amelia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to examine the effect of corporate multinationality, occurance of transactions with tax-haven-countries, and intangible assets on transfer pricing aggressiveness in Indonesian companies. Applying purposive sampling method, this study analyzed 100 samples of multinational companies listed in the Indonesia Stock Exchange (IDX) during the period from 2015 to 2019, except companies from the financial and insurance sector. Applying multiple regression analysis, this study unveiled a positive and significant impact of multinationality, occourance of transactions with tax-haven-countries, and intangible assets on companiess transfer pricing aggressiveness.